Qualidade, compostos bioativos e atividade antioxidante de frutos de Physalis sp - Silva, Polyana Barbosa da (2013)
Physalis ou golden berry, genus of the Solanaceae family, is widely distributed throughout North and Northeast of Brazil. Known as Canapu, Camapum, Joá-de-capote, among other popular names, occurs spontaneous, needing studies on quality of fruits. Therefore, this study aimed to evaluate the quality, bioactive compounds, and antioxidant activity of the species Physalis angulata and P. pubescens harvested from six localities in the state of Paraíba, comparing with a commercial species (P. peruviana). Fruits without the calix were classified into five maturity stages: Completely Green (CG), Light Green (LG), Begining of Yellow Pigmentation (BY), Predominantly Yellow (PY), and Completely Yellow (CY). The evaluatins were: fresh mass (g), length (mm) diameter (mm), firmness (N), color, pH, soluble solids (SS%), Titratable Acidity (TA% citric acid), SS / TA ratio, Reducing Sugars and total soluble sugars (TSA, g.100g-1), ascorbic acid (AA, mg.100g-1), total carotenoids (μg.100g-1), total chlorophyll (mg.100g-1), yellow flavonoids (mg.100g-1), anthocyanins (mg.100g-1), Total Extractable Polyphenols (TEP mg 100g-1), and Total Antioxidant Activity (TAA g.gDPPH-1). It was applied a completely randomized design in a factorial scheme (location x maturity stage), being for P. angulata in a 4x5 and for P. pubescens in a 2x4. For physical assessments, it was used 40 fruits, consisting of 40 repeplications and for the other evaluations it was used three replications, each one using a number of fruit corresponding to approximately 200 g without the floral calyces. Data were submitted to variance analysis and the means of the local (L1, L2, L3, L4, L5, and L6) and maturity stages were compared by the Tukey test. A comparison of P. peruviana with the two species occurring in Paraíba was performed by Dunnett's test at 5% probability. The SS of P. angulata fruits from L2 and L4 were superior to those of commercial species. Only the AT of P. pubescens fruits from L6 was higher than the P. peruviana. The SS / TA ratio was higher than the commercial in fruits from all locations, except the L6, which may favor the consumption as fruits fresh. The AR content in fruits of P. angulata and P. pubescens were lower than the P. peruviana. The AST in fruits of P. angulata and P. pubescens differed from the P. peruviana (9.90 g.100g-1), except the fruits of P. angulata from L2 (9.40 g.100g-1). Fruits from L2 showed ascorbic acid close to the P. peruviana, being higher than those from other locations. Fruit with the highest content of total carotenoids, chlorophyll, flavonoids, and anthocyanins were of P. pubescens, from L6. This species also showed higher content of TEP than the fruits of P. angulata and P. peruviana and total antioxidant activity close to this last. Fruits of P. pubescens presented higher contents of bioactive compounds than those of P. angulata, excepted by ascorbic acid in fruits of the L2, which was higher than those from other locations and very close to the P. peruviana. Fruits of P. pubescens also showed higher antioxidant activity that of P. Angulata, being close to that of P. peruviana.